Supramolecular synthon hierarchy in bumetanide cocrystals - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Novel cocrystals of sulfonamide drug Bumetanide with carboxamides are developed based on supramolecular synthons approach

Syringic acid: structural elucidation and co-crystallization - Thipparaboina, Rajesh; Mittapalli, Sudhir; Thatikonda, Sowjanya; Nangia, Ashwini; Naidu, V. G. M.; Shastri, Nalini R. (Crystal Growth & Design, 2016)
Syringic acid (SYRA) is a potential antioxidant used in traditional Chinese medicine and is an emerging nutraceutical. Current reports claim its potential anti-angiogenic, anti-glycating, anti-hyperglycaemic, neuroprotective, and memory-enhancing properties in various animal models. To date, SYRA crystal structure has not been elucidated, and no crystal engineering studies have been reported. This study reports the crystal structure of SYRA for the first time along with its nicotinamide (SNCT-E) and urea (SU-EA-M) co-crystals. All forms were successfully characterized using single crystal X-ray diffraction (XRD), powder XRD, and differential scanning calorimetry. Single crystal analysis revealed that SYRA crystallized in the C2/c space group, whereas SNCT-E (2:1) and SU-EA-M (1:2) crystallized in the P21/n and Cmca space group, respectively. Novel co-crystals have shown improved solubility, modified dissolution profiles, and improved flow and compressibility. Cytotoxic effects were explored in DU145 prostate cancer cell lines for the first time, and significant enhancement in cytotoxicity by the co-crystals was observed compared to plain components. A two-fold increase in % cytotoxicity of SNCT-E was observed when compared to the corresponding physical mixture. These studies shed light on potential utility of SYRA as a coformer for various pharmaceutical applications to design synergistic and organ-protective co-crystals.

Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.

Salts and salt cocrystals of the antibacterial drug pefloxacin - Gunnam, Anilkumar; Suresh, Kuthuru; Nangia, Ashwini (Crystal Growth & Design, 2018)
Pefloxacin (PEF) is an amphoteric, antibacterial drug which exists as a neutral molecule in the crystal structure stabilized by C-H center dot center dot center dot O and C-H center dot center dot center dot F interactions. The design of multicomponent solids using crystal engineering was undertaken in a cocrystal/salt screen of PEF with generally recognized as safe (GRAS) dicarboxylic acids to improve the solubility and phase stability of the drug. Ten multicomponent forms, namely, five salts, two salt hydrates, and three salt cocrystals, were prepared by liquid-assisted grinding followed by crystallization. In some cases, salt and salt cocrystals were obtained concomitantly during solution evaporative crystallization. Single crystal X-ray diffraction showed that the structures are stabilized by N+-H center dot center dot center dot O-, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot F, and pi-pi stacking interactions. The bulk phase purity of multicomponent forms was characterized by powder X-ray diffraction, spectroscopy, and thermal techniques. The salt/salt cocrystal forms exhibit a faster dissolution rate and higher solubility compared to pure PEF in pH 1.2 (acidic, like gastric environment) and pH 7 phosphate buffer media (neutral, like intestinal passage). Specifically the PEF+-SA(-) salt (SA = succinic acid) showed remarkably high solubility, dissolution rate, and stability compared to the other multicomponent forms and PEF neutral form. The drug formulation compatible pefloxacin succinate is a promising soluble and stable PEF salt.

Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Supramolecular synthon hierarchy in sulfonamide cocrystals with syn-amides and N-oxides - Bolla, Geetha; Nangia, Ashwini (IUCRJ, 2019)
Sulfonamide drugs are well known antibacterial and antimicrobial molecules for pharmaceutical development. Building a library of suitable supramolecular synthons for the sulfonamide functional group and understanding their crystal structures with partner coformer molecules continues to be a challenge in crystal engineering. Although a few sulfonamide cocrystals with amides and N-oxides have been reported, the body of work on sulfonamide synthons is limited compared with those that have carboxylic acids and carboxamides. To address this structural gap, the present work is primarily focused on sulfonamide-lactam and sulfonamide-syn-amide synthons with drugs such as celecoxib, hydrochlorothiazide and furosemide. Furthermore, the electrostatic potential of previously reported cocrystals has been recalculated to show that the negative electrostatic potential on the lactam and syn-amide O atom is higher compared with the charge on carboxamide and pyridine N-oxide O atoms. The potential of sulfonamide molecules to form cocrystals with syn-amides and lactams are evaluated in terms of the electrostatic potential energy for the designed supramolecular synthons.
Keywords: cocrystals; crystal engineering; sulfonamides; supramolecular synthons; syn-amides

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.